2021
DOI: 10.1007/s42770-021-00532-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Bombyx mori gloverin on intestinal epithelial cells exposure to enterotoxigenic E. coli

Abstract: Bombyx mori gloverin A2 (BMGlvA2) is an induced antimicrobial insect protein isolated from Bombyx mori. This study was conducted to explore the effect and potential mechanisms of BMGlvA2 on inflammatory responses and cellular functions in intestinal epithelial cells (IPEC-J2) exposure to enterotoxigenic E. coli (ETEC). IPEC-J2 cells pretreated with or without BMGlvA2 (12.5 μg/mL) were challenged by ETEC K88 (1×10 6 CFU/well) or culture medium. We show that BMGlvA2 pretreatment increased the cell viability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The observed gradual transition in the microbial community's composition, marked by the co-dominance of the Proteobacteria and Actinobacteria phyla, underscores the resilience and adaptability of the gut microbiota. This capacity for adaptation is vital for silkworms to manage the challenges associated with shifting from an artificial to a natural diet, which encompasses adjustments in nutrient composition, digestibility, and the introduction of plant secondary metabolites [22,32].…”
Section: Discussionmentioning
confidence: 99%
“…The observed gradual transition in the microbial community's composition, marked by the co-dominance of the Proteobacteria and Actinobacteria phyla, underscores the resilience and adaptability of the gut microbiota. This capacity for adaptation is vital for silkworms to manage the challenges associated with shifting from an artificial to a natural diet, which encompasses adjustments in nutrient composition, digestibility, and the introduction of plant secondary metabolites [22,32].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the intestinal porcine epithelial cell (IPEC-J2) is an efficient cell model for the examination of the underlying mechanism behind the host anti- E. coli F18 pathogen [ 7 , 20 ]. In addition, multiple studies have revealed that the IPEC-J2 exposure to E. coli triggers oxidative damage and inflammatory responses, which results in enhancing apoptotic cell death and diminishing functionality [ 21 , 22 , 23 ]. Nevertheless, the explicit biological role of m 6 A regulators in conferring resistance against E. coli F18-based infection in IPEC-J2 cells remains undetermined.…”
Section: Introductionmentioning
confidence: 99%